2021
DOI: 10.3390/antiox10020209
|View full text |Cite
|
Sign up to set email alerts
|

Native High-Density Lipoproteins (HDL) with Higher Paraoxonase Exerts a Potent Antiviral Effect against SARS-CoV-2 (COVID-19), While Glycated HDL Lost the Antiviral Activity

Abstract: Human high-density lipoproteins (HDL) show a broad spectrum of antiviral activity in terms of anti-infection. Although many reports have pointed out a correlation between a lower serum HDL-C and a higher risk of COVID-19 infection and progression, the in vitro antiviral activity of HDL against SARS-CoV-2 has not been reported. HDL functionality, such as antioxidant and anti-infection, can be impaired by oxidation and glycation and a change to pro-inflammatory properties. This study compared the antiviral activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 49 publications
3
75
0
2
Order By: Relevance
“…The little data existing seems to suggest two different roles for PON1 in COVID-19, depending on whether it is present in the circulation or within cells. Purified native HDL with intact PON1 elicits a potent antiviral effect against SARS-CoV-2 in cultured monocyte cells, while glycated HDL, with inactive PON1, loses the antiviral activity [ 24 ]. However, an in silico study reported that PON1 enhances the action of ACE2, the main cell receptor of SARS-CoV-2 [ 25 ], and the inhibition of PON1 activity has been reported as a potent inhibitor of vaccinia virus protein synthesis and viral mRNA methylation in mice [ 26 ], suggesting that intracellular PON1 is important in the translation of viral proteins and virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…The little data existing seems to suggest two different roles for PON1 in COVID-19, depending on whether it is present in the circulation or within cells. Purified native HDL with intact PON1 elicits a potent antiviral effect against SARS-CoV-2 in cultured monocyte cells, while glycated HDL, with inactive PON1, loses the antiviral activity [ 24 ]. However, an in silico study reported that PON1 enhances the action of ACE2, the main cell receptor of SARS-CoV-2 [ 25 ], and the inhibition of PON1 activity has been reported as a potent inhibitor of vaccinia virus protein synthesis and viral mRNA methylation in mice [ 26 ], suggesting that intracellular PON1 is important in the translation of viral proteins and virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HDL-C can regulate innate and adaptive immunity, thereby increasing resistance to viral infections ( 31 ). In addition, a recent study showed that HDL-C has antiviral activity against SARS-CoV-2 ( 32 ). Decreased HDL-C levels during hospitalization have been reported as a sign of poor prognosis for COVID-19 patients ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decreased content in PON1 and an increased content of SAA and alpha-1 antitrypsin compared to control subjects are associated with impaired ability of HDL-mediated to inhibit the apoptosis of endothelial cells [ 122 ]. In vitro, glycation impairs the inhibitory activity of HDL towards SARS-CoV-2 infection of epithelial cells [ 153 ]. Whether or not infection of endothelial cells with SARS-CoV2 is inhibited by HDL and disturbed by glycation remains to be investigated.…”
Section: Hdl and Endothelial Cell Dysfunctionmentioning
confidence: 99%